Study of prescribing pattern of topical corticosteroids in dermatology out patients department in a tertiary care hospital in India - Nerurkar, Rajan P.; Kokane, Manish R.; Mehta, Manthan Nikesh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The selection of rational yet most effective treatment is an art to be learnt by most physicians. The advent of topical glucocorticoids has changed the way inflammatory dermatological conditions are managed. However, there is a constant need to keep a check on these prescriptions for their rationality. The present study was done to review the prescribing pattern of topical corticosteroids in dermatology outpatients at a tertiary care hospital. Methods: This was a prospective observational study on 300 prescriptions of patients above 18 years of age receiving topical corticosteroids in the dermatological outpatient department of a tertiary care hospital in the time frame of June 2014 to August 2014. Data obtained was recorded in a structured case record form (CRF) and analysed for their prescribing pattern, adverse reactions and cost analysis within different socioeconomic classes. Data was analysed using relevant statistical tests. A P-value of less than 0.05 was considered significant. Results: Data was collected from 300 patients with the mean age of 38.28±11 years. The most common indication for prescription of topical steroids was eczema (22.33%). The most commonly prescribed topical steroid was clobetasol (68.66%) followed by mometasone (11%), betamethasone (9.33%) and halobetasol (3%). Cream was the most frequently prescribed formulation (85.66%). 28 patients (9.33%) out of 300 showed adverse drug reactions, of which, erythema was the most common (50%). Conclusions: Topical corticosteroids are effective drugs in an array of dermatological diseases and abundant choices are available in different formulations. Optimal therapy involves careful consideration of factors such as potency, formulation, responsiveness and the cost of the topical steroid.